Brazil: Between the Alternative Modernity and the Alternative to Modernity - Thiago Aguiar Simim; Daniel Carvalho Ferreira (Íconos)
This article analyzes the critique of modernity in Latin American social thought from two conceptions: Walter Mignolo’s position in the modernity/coloniality group, and the critique of the Brazilian sociologist Jessé Souza to readings about non-modernity in Brazil. The critique of these two perspectives sheds light on the particular position of Brazil: on one hand, its situation can be analyzed from the broad perspective of Latin America; or on the contrary, the country presents peculiarities that make difficult the task of making a simple overview. The nodal point between these interpretations is in the conception of peripheral and alternative modernity (or modernization), and in the role that this concept plays in both theories.